ANALYSIS OF THE MEANING OF CONNOTATIONS IN THE SONG LUGHAT AL-AALAM BY KHUMOOD EL-KHUDER - Munawaroh, Izati; Danil, M; Wahyudi, Jarot (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
Semantic is the study of the meaning of words. In the lyrics of the song Luhgat Al-A'lam by Humood Alkhuder presents a deep meaning about the sacrifice and love of a mother is very great. The meaning of the connotation contained in each lyric of Luhgat Al-A'lam song is able to bring out a deep taste value so that it becomes a memorable song for the listener. This research uses qualitative research methods. Qualitative research is research that produces descriptive data in the form of written words. The technique used to obtain data is to use reading techniques and recording techniques. that is, describing and explaining the meaning of connotations in the song Luhgat Al-A'lam by Humood Alkhuder. The meaning of the connotation in the song Luhgat Al-A'lam as beriku: mother as a place of home for a child. A mother who protects and rescues her child under any circumstances. Mother is like the nectar of the most precious part of a flower, in the sense that a mother has the most noble position, which is held in high esteem, and which has a higher glory than the father.